2011
DOI: 10.1080/10538720.2011.588930
|View full text |Cite
|
Sign up to set email alerts
|

Sexual-Minority Women and Alcohol: Intersections Between Drinking, Relational Contexts, Stress, and Coping

Abstract: Few studies explore sexual minority women’s experiences and perceptions of alcohol. Qualitative interviews were conducted with six sexual minority women who reported having sought help for alcohol problems in the past and six who did not. Themes emerged in two broad areas: stressors that contributed to heavy or problem drinking and factors that enhanced coping and reduced both stress and problem use. Alcohol use across groups was framed in terms of social context (e.g., bar patronage), stress management, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 54 publications
5
36
1
Order By: Relevance
“…Although representations across groups were similar, some representations, such as alcohol use in fostering community connection and mediating stress, appeared to be particularly salient for sexual minority women. These findings are congruent with other qualitative studies of sexual minority women that describe the role of alcohol in managing stress and anxiety and facilitating social interaction (Cogger, Conover, & Israel, 2012; Condit et al, 2011; Reyes, 1998). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although representations across groups were similar, some representations, such as alcohol use in fostering community connection and mediating stress, appeared to be particularly salient for sexual minority women. These findings are congruent with other qualitative studies of sexual minority women that describe the role of alcohol in managing stress and anxiety and facilitating social interaction (Cogger, Conover, & Israel, 2012; Condit et al, 2011; Reyes, 1998). …”
Section: Discussionsupporting
confidence: 89%
“…To date, a few qualitative studies have explored the experiences of sexual minorities and how they perceive the role of alcohol in relation to their lives, identities, and social contexts and are helpful in understanding both normative use of alcohol and disparities in risk for alcohol problems among sexual minority women. These studies point to the importance of social drinking contexts in providing safety and community support (Condit, Kitaji, Drabble, & Trocki, 2011; Gruskin et al, 2006; Reyes, 1998) and self-acceptance (Parks, 1999). Parks (1996) found that lesbian women were most likely to describe heavier use of alcohol or drugs in two time periods: when they were becoming aware of their attraction to women, but had not yet become involved in the lesbian community and when they began to immerse themselves in the lesbian community.…”
Section: Introductionmentioning
confidence: 99%
“…Research to date on alcohol-related problems among sexual minorities has focused disproportionately on risk factors, neglecting exploration of possible factors that may be protective against substance use (Balsam, 2003; Condit et al, 2011; Hughes et al, 2003; Kwon, 2013). Religion is generally recognized as a protective factor against hazardous drinking and the development of alcohol use disorders among both adults and adolescents (Allen and Lo, 2010; Borders et al, 2010; Edlund et al, 2010; Haber et al, 2012; Michalak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, drinking locations (e.g., bars, clubs) have been social centers for lesbian, gay, bisexual, transgender, and queer (LGBTQ) people and qualitative studies have highlighted their influence on drinking (Condit, Kitaji, Drabble, & Trocki, 2011; Gruskin, Byrne, Kools, & Altschuler, 2006). In fact, compared to heterosexual women, lesbian/bisexual women spend more time at bars/parties and bisexual women drink more alcohol in both locations (Trocki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Given that drinking is influenced by the extent to which it is perceived as normative and acceptable (Cullum, O’Grady, Armeli, & Tennen, 2012; Thombs et al, 1997), identifying where and with whom SMW drink can improve our understanding of contextual influences on drinking and, in turn, inform prevention and intervention efforts. Finally, research has focused on lesbians (Parks, Hughes, & Kinnison, 2007) or SMW (Condit et al, 2011) without examining differences between lesbians and bisexual women. Bisexual women are at particularly high risk for problematic drinking (McCabe et al, 2009), lack of support from LGBTQ individuals (Hequembourg & Brallier, 2009), and face prejudice from heterosexual and gay/lesbian individuals (Brewster, Moradi, Deblaere, & Velez, 2013).…”
Section: Introductionmentioning
confidence: 99%